Three-Dimensional Human Skin Equivalent as a Tool To Study Acinetobacter baumannii Colonization - de Breij, Anna (American Society for Microbiology, 2012)
Acinetobacter baumannii can colonize body surfaces of hospitalized patients. From these sites, invasion into the host and spread to other patients and the hospital environment may occur. The eradication of the organism from the patient's skin is an important infection control strategy during epidemic and endemic episodes. In this study, a three-dimensional (3D), air-exposed human epidermal skin equivalent was exploited to study Acinetobacter skin colonization. We characterized the adherence of A. baumannii ATCC 19606(T) and Acinetobacter junii RUH2228(T) to and biofilm formation on the skin equivalent and the responses to these bacteria. Furthermore, we assessed the ability of the disinfectant chlorhexidine to decolonize the skin equivalents. The results revealed that both strains replicated on the stratum corneum for up to 72 h but did not invade the epidermis. A. baumannii, in contrast to A. junii, formed large biofilms on the stratum corneum. Bacterial colonization did not affect keratinocyte activation, proliferation, or differentiation, nor did it induce a strong inflammatory response. Disinfection with chlorhexidine solution resulted in complete eradication of A. baumannii from the skin, without detrimental effects. This 3D model is a promising tool to study skin colonization and to evaluate the effects of novel disinfectant and antimicrobial strategies.